Comparative Study of the Elements of Qulubun Ya'qilun and Qulubun La Yafqahun in Qs. Al-A'raf Verse 179 And Al-Hajj Verse 46 - Abror, M.Qusyairi; Sassi, Komarudin (Westscience Press, 2025)
This research aims to examine and compare the elements contained in the phrases